A bite wound from a stray or feral cat: Case report - Katica Muhamed; Obradović Zarema; Abdalaziz Mohamed Rowida Seifeldin; Bajrić Amela; Lučkin Amina (Halo 194, 2022)
Introduction/Objective Cat bites can seriously harm human health, especially if the bite comes from a stray or feral cat who is not under veterinary supervision. Cat bites are the second most common mammal bites, second only to dog bites, and responsible for ¾ of all bites that result in infection. We are presenting the case of a young woman whose hand had been bitten by a stray or feral cat. The objective of this case study is to stress the importance of timely medical treatment and wound management based on guidelines for treating bites inflicted by stray or feral cats, aiming to prevent possible complications. Case report A 32-year-old woman was admitted and examined in the University of Sarajevo Clinical Centre Emergency Department on the third day after being bitten by a stray or feral cat, by which time all signs of inflammation had already developed at the site of the injury-her right hand. Medical help was provided based on guidelines that included specific wound dressings recommended for animal bites, a prescription of antibiotics, analgesics and an anti-tetanus shot. The patient fully recovered with no complications. Conclusion The specific anatomy of the cat's canines enables them to penetrate deeply into the bitten tissue, which can cause an innoculation of a wide range of microorganisms from the cat's mouth into the patient's bloodstream. This can cause serious inflammatory processes, especially in immunocompromised patients. Adequate medical treatment of injuries resulting from cat bites is necessary as soon as possible, but no later than 48 hours after the incident.